Production Engineering - Reservoir Pressures in the Hobbs Field, New Mexico (With Discussion) - R. S. Christie (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1932)
Reservoir pressure is the pressure at which a fluid is held in a state of equilibrium in a porous stratum. This pressure may be a result of the genesis of oil or gas and its subsequent migration into and through an adjacent porous stratum, or of hydraulic head. Reservoir pressure is an indication of the potential energy contained in the reservoir, and when it is known the engineer is in a position to use it to advantage in recovering and lifting the oil. It is important to know the pressures in any type of reservoir, but this knowledge is probably of greater value in a limestone reservoir, as at Hobbs, where producing rates or conditions may be more sensitive to changes in pressures. The Hobbs field is in east central Lea County, New Mexico. The discovery well was completed by the Midwest Refining C I. in 1928, but intensive development did not begin until after the completion by the Humble Oil and Refining Co. of No. 1-A Bowers in February, 1930. There are 143 producing wells on approximately 5500 acres. The field has not been defined to the northwest, but a projection of structural contours indicates that the productive area ultimately may cover 7500 acres. The producing horizon is the White or Crystalline lime of Permian age. The top of the lime is found at an average depth of 4000 ft. and the wells penetrate it an average distance of 200 ft. The main pay zone is an oolitic stratum about 25 ft. below the top, and varies from 2 to 15 ft. in thickness. Other porous or cavernous strata are found lower in the lime but have little saturation. The initial production varied from 100 to 25,000 bbl. per day, depending perhaps to some extent on the structural location but chiefly on the porosity of the pay. The initial gas-oil ratio varied from 325 to 16,000 cu. ft. per barrel. In wells where the top of the White lime was found below 350 ft. below sea level (Fig. 1)) the gas-oil ratio was usually less than 1500 cu. ft. per barrel, while in wells higher than 350 ft. below sea level, the ratio was usually above 2000 cu. ft. per barrel. The water table has been determined at about 620 ft. below sea level, by three wells on the west side of the field. With few exceptions, the wells have been completed with 7-in. casing cemented